Disaster relief operations: past, present and future - Dubey, Rameshwar; Gunasekaran, Angappa; Papadopoulos, Thanos (Annals of operations research, 2019)
The aim of the preface is to introduce the scope of this special issue (SI). We explain our editorial approach and summarise our findings based on articles included in this SI. Finally, we outline future research questions which stemmed out of the discussions of this SI.